Political Economy of Renewable Energy and Scenarios for Iran in the Energy Transition to 2050 Outlook - Ali Esmaeili Ardakani; Morteza Shokri (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2022)
In recent years, the share of renewables in the global energy basket has increased significantly. This will have geopolitical consequences, especially for a country like Iran, whose economy is largely dependent on fossil fuel revenues. By examining the transition process of the global and regional economy towards renewable and clean energy, this article tries to outline Iran's position in the energy transition perspective. The main question is: how will Iran position itself in the global energy transition outlook to 2050? Through scenario planning, the authors identified four possible scenarios, including "meeting sustainable development and transition to green gold", "gradual and independent transition to sustainable development and green gold", "development based on black gold" and "development locked with black gold". They cover a wide range of possible futures. By knowing these scenarios and comparing their desirability, policymakers will be able to properly assess the costs and opportunities of the transition to clean energy in different situations.s